MiR‐587 promotes cervical cancer by repressing interferon regulatory factor 6. (10th September 2020) - Ren, Yuefang; Dong, Jie; He, Pingya; Liang, Yufei; Wu, Lifang; Wang, Jiajian; Chu, Boliang
Abstract: Background: Interferon regulatory factor 6 (IRF6) exhibits tumor‐suppressive functions in several cancer types. In the present study, the antitumor properties and related pathway mechanism of IRF6 were investigated in cervical cancer. Methods: Forty‐one pairs of cervical cancer specimens and para‐carcinoma tissues were collected to evaluate IRF6 expression using immunohistochemical staining and miR‐587. The effects of miR‐587 and IRF6 on cervical cancer cell growth were explored by MTT assays and in a HeLa tumor xenograft mouse model. The migration and invasion of cervical cancer cells were monitored using transwell assays. Results: IRF6 expression in cervical cancer specimens and cell lines was significantly reduced compared to that in the corresponding control group. In addition, IRF6 expression was negatively correlated with miR‐587 in cervical cancer tissues. Bioinformatics algorithms and luciferase assays revealed that IRF6 is a potential target of miR‐587, and miR‐587 mimic transfection led to a significant repression of IRF6 protein levels in cervical cancer cells. We also discovered that the antineoplastic properties of IRF6 could be reversed by overexpressing miR‐587 in cervical cancer cells. The up‐regulation of miR‐587 was correlated with poor overall survival in cervical cancer. In an in vivo experiment, miR‐587 silencing induced HeLa tumor growth inhibition, which was associated with the up‐regulation of IRF6 protein in the tumor. Conclusions: miR‐587 post‐transcriptionally represses IRF6 protein expression to abrogate the antineoplastic activity of IRF6. The miR‐587/IRF6 signaling pathway plays a crucial role in the progression of cervical cancer and serves as a potential therapeutic target for the treatment of cervical cancer. Abstract : Interferon regulatory factor 6 (IRF6) was down‐regulated in cervical cancer, and patients with IRF6 low expression showed a shorter overall survival compared to those patients with IRF6 high expression.